The Influence of Marketing Mix on Purchase Intention with Customer Attitude as a Mediating Variable (A Case Study of a New Men's Fashion Retail Business in Surabaya) - Suci Sukmajaya Rizky; Atik Aprianingsih (UNIVED Press, 2024)
Indonesia's textile and apparel industry is experiencing a significant demand, with an anticipated GDP increase of 2022. Surabaya, a major city in Indonesia, is well-positioned to capitalize on this opportunity by establishing a retail business catering to the lower-middle-class segment of the men's fashion industry. This study aims to help entrepreneurs in Surabaya identify factors influencing their decision to establish a retail business in the men's fashion sector using the SEM-PLS method. The research investigates the purchase intentions of men of productive age from the lower-middle-class demographic and the potential marketing mix strategies for businesses in the Surabaya men's fashion sector. Findings from 230 respondents showed that product, place, and promotion variables significantly influence customer attitude, which in turn influences purchase intention. However, price does not significantly influence customer attitude. The study suggests that price, product, and promotion variables can be partially mediated by customer attitude, while the place variable can be fully mediated.